The Pressor Response to Concurrent Stimulation of the Mesencephalic Locomotor Region and Peripheral Sensory Afferents Is Attenuated in Normotensive but Not Hypertensive Rats - Liang, Nan; Iwamoto, Gary A.; Downey, Ryan M.; Mitchell, Jere H.; Smith, Scott A.; Mizuno, Masaki (Frontiers in Physiology, 2019)
Central command (CC) and the exercise pressor reflex (EPR) regulate blood pressure during exercise. We previously demonstrated that experimental stimulation of the CC and EPR pathways independently contribute to the exaggerated pressor response to exercise in hypertension. It is known that CC and EPR modify one another functionally. Whether their interactive relationship is altered in hypertension, contributing to the generation of this potentiated blood pressure response, remains unknown. To address this issue, the pressor response to activation of the CC pathway with and without concurrent stimulation of the EPR pathway, and vice versa, was examined in normotensive Wistar Kyoto (WKY) and spontaneously hypertensive (SHR) rats. In decerebrated, paralyzed animals, activation of the CC pathway was evoked by electrical stimulation of the mesencephalic locomotor region (MLR; 20-50 μA in 10-μA steps). Electrical stimulation of the sciatic nerve (SN, 3, 5 and 10x motor threshold; MT) was used to activate hindlimb afferents known to carry EPR sensory information. In both WKY and SHR, the algebraic sum of the pressor responses to individual stimulation of the MLR and SN were greater than when both inputs were stimulated simultaneously. Although the blood pressure response to a constant level of SN stimulation was not significantly affected by concurrent MLR stimulation at variable intensities, the pressor response to a constant level of MLR simulation was significantly attenuated by concurrent SN stimulation in WKY but not in SHR. These findings suggest the interactive relationship between CC and the EPR is inhibitory in nature in both WKY and SHR. However, the neural occlusion between these central and peripheral pressor mechanisms is attenuated in hypertension.